Germicidal effect of intense pulsed light on Pseudomonas aeruginosa in food processing - Liang, Jinglong; Huang, Teng Yi; Li, Xuejie; Gao, Yan (Frontiers in Microbiology, 2023)
Background: Pseudomonas aeruginosa (P. aeruginosa) can cause serious infections in many parts of the body and is also an underestimated foodborne pathogen. Intense pulsed light sterilization is recognized for its high sterilization efficiency, flexible and safe operation and ease of installation on production lines, which makes up for the shortcomings of several other physical sterilization technologies. Methods: This experiment studied the killing efficiency of different capacitances (650 μF, 470 μF, 220 μF) of intense pulsed light on foodborne pathogenic microorganisms P. aeruginosa in the models of liquid food models, 96-well cell plates, and polycarbonate membrane models at room temperature (25°C) and refrigerated (4°C) environments to provide data to support the application of IPL sterilization devices in food processing. Results: The IPL was very effective in killing P. aeruginosa in the planktonic state as well as in the early and mature biofilm states, meeting target kill rates of 100%, 99.99% and 94.33% for a given number of exposures. The biofilms formed in the polycarbonate membrane model and the 96-well plate model were more resistant to killing compared to the planktonic state. To achieve the same bactericidal effect, the number of flashes increased with decreasing capacitance. Conclusions: The bactericidal effect of IPL on P. aeruginosa was significantly influenced by the state of the bacterium. The larger the capacitance the higher the number of pulses and the better the sterilisation effect on P. aeruginosa.